Understanding Dengue Transmission: Application of an Eco health Approach in Dhaka, Bangladesh. - Chowdhury,Parnali Dhar (2015)
ABSTRACT: Affected by unprecedented urban growth, overcrowding, poverty, and health inequalities, Bangladesh has remained hyperendemic for dengue since 2000. Considering the complexities involved with dengue transmission, I argued that understanding transmission requires encapsulating different disciplinary knowledge as well as non-academic knowledge. I have applied an Ecohealth approach to investigate dengue transmission dynamics in Dhaka, Bangladesh. Using the Delphi method, all 90 Wards of Dhaka were classified into 'high', 'medium', and 'low' Socio-Economic Status (SES) zones. A total of 1,200 households were randomly selected which represented the SES zones. During 2011-2012, these sampled households were repeatedly inspected for Aedes mosquitoes and to collect blood samples from residing members. This transdisciplinary investigation focused on: i) the rates of human exposure to dengue virus (DENV) by identifying individuals with IgM and IgG antibodies in the serosurvey samples; ii) abundance of dengue vector mosquitoes (Aedes aegypti) in the same households; iii) risk perception, and Knowledge, Attitude and Practice (KAP) regarding dengue among community members and experts. KAP survey results indicated that 93.7% of the community members knew that mosquitoes act as the primary vector of its transmission; 87.3% were unaware that Aedes mosquitoes prefer to lay their eggs in water containers. The entomological survey results showed that 26.7% of all surveyed houses in the city were infested with Aedes aegypti mosquitoes. The ornamental functional categories of containers were most significant containers in producing maximum number of Aedes pupae; this was found to be a significant risk factor for seroprevalence and seroconversion. The examination of IgG seroprevalence iv revealed that seropositivity was strongly correlated with increased age and number of indoor potted plants. The serosurvey findings showed that seroprevalence was high (79.9%), revealing that most dwellers had been exposed DENV. However, there was no significant association between Aedes positive houses and houses with seroconverted persons, indicating that people were being infected in distant areas outside their houses. A persistently high rate of dengue infection in Dhaka is being influenced by the lack of knowledge and awareness of the eco-bio-social factors. Improvement in intersectoral coordination to formulate and implement dengue epidemic prevention and control interventions is necessary.